2005
DOI: 10.1109/tasc.2005.849617
|View full text |Cite
|
Sign up to set email alerts
|

An Axial Gap-Type HTS Bulk Synchronous Motor Excited by Pulsed-Field Magnetization With Vortex-Type Armature Copper Windings

Abstract: We studied a high-temperature superconducting synchronous motor assembled with melt-textured Gd-Ba-Cu-O bulk field magnets. The motor is an axial gap-type, brushless synchronous motor with eight rotating bulk field magnet poles. Liquid nitrogen is circulated to cool down the rotor components. Pulsed field magnetization was performed to excite the bulk field magnets by using a pair of the vortex-type armature copper windings under the zero-field cooling. The trapped peak field density on the surface of the bulk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
55
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(56 citation statements)
references
References 7 publications
0
55
0
Order By: Relevance
“…Large single-domain RE-Ba-Cu-O superconductors are promising materials for cryogenic applications due to their superior superconducting performance [1,2,3]. For the commercialization, it is important to keep the low cost to fabricate while being the high superconducting properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large single-domain RE-Ba-Cu-O superconductors are promising materials for cryogenic applications due to their superior superconducting performance [1,2,3]. For the commercialization, it is important to keep the low cost to fabricate while being the high superconducting properties.…”
Section: Introductionmentioning
confidence: 99%
“…The corresponded nano-sized inclusions and defects in the superconducting matrix are effective as pinning centers to improve J C of melt-growth bulk superconductors REBa 2 Cu 3 O 7-δ (RE123) [4][5][6][7][8][9]. It is reported that the additions of nano-sized SnO 2 or ZrO 2 to RE123 matrix, as second phase with Gd211 inclusions, form a three-dimensional band structure to enhance J C [8]. Lau et al observed that the Ag-sheathed Bi(Pb)-Sr-Ca-Cu-O tapes with magnetic nano-powder γ-Fe 2 O 3 increase the pining strength [11].…”
Section: Introductionmentioning
confidence: 99%
“…A small-size synchronous machine with Gd-123 bulk-HTS pole-field magnets aimed at the sub-MW class of ship propulsion motors has been constructed in 2002. The evaluation test was conducted in 2003, and a 3.1 kW output with 720 rpm was reported [4]. On the other hand, the machine designed with the Bi-2223 HTS winding offers the convenience of increasing the magnetic flux as a function of applied DC current.…”
Section: Introductionmentioning
confidence: 99%
“…Since the bulk magnet can generate strong magnetic field exceeding 2 T that is the limit of ordinary iron-cored electromagnets by compact device in a low running cost, various industrial applications such as motor/generator [2], magnetron spattering [3], drug delivery system (DDS) [4] and magnetic separation [5,6] are considered. To propagate an industrial application of bulk magnet in the feature, it is necessary to enhance a magnetic force, as well as amplitude of magnetic field.…”
Section: Introductionmentioning
confidence: 99%